2007
DOI: 10.1016/j.nlm.2006.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Blunted hippocampal, but not striatal, acetylcholine efflux parallels learning impairment in diencephalic-lesioned rats

Abstract: A rodent model of diencephalic amnesia, pyrithiamine-induced thiamine deficiency (PTD), was used to investigate the dynamic role of hippocampal and striatal acetylcholine (ACh) efflux across acquisition of a nonmatching-to-position (NMTP) T-maze task. Changes in ACh efflux were measured in rats at different time points in the acquisition curve of the task (early= day 1, middle = day 5, and late = day 10). Overall, the control group had higher accuracy scores than the PTD group in the latter sessions of NMTP tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 66 publications
(86 reference statements)
3
31
0
Order By: Relevance
“…However, there was a similar increase in striatal ACh efflux in both groups suggesting there was no striatal cholinergic dysfunction following PTD treatment. Thus, similar to the data obtained by Roland and Savage (2007) using a matching to position task, ACh functioning in the striatum appeared to be spared and functional during spontaneous alternation testing following PTD treatment. It should be noted that spontaneous alternation has been shown to rely heavily upon an intact and functional hippocampal system and that this task is sensitive to fluctuations of ACh in the hippocampus (McIntyre et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…However, there was a similar increase in striatal ACh efflux in both groups suggesting there was no striatal cholinergic dysfunction following PTD treatment. Thus, similar to the data obtained by Roland and Savage (2007) using a matching to position task, ACh functioning in the striatum appeared to be spared and functional during spontaneous alternation testing following PTD treatment. It should be noted that spontaneous alternation has been shown to rely heavily upon an intact and functional hippocampal system and that this task is sensitive to fluctuations of ACh in the hippocampus (McIntyre et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…The data replicate that PTD rats have impaired hippocampal ACh release that is evident only under conditions of spatial exploration or place learning [46,49]. In addition, the unbiased stereological estimate of cell counts also replicates the profile counting method of assessment of loss of ChAT immunopositive cells in the MS/DB of PTD treated rats [43,44].…”
Section: Discussionsupporting
confidence: 69%
“…Using a rodent model of WKS, pyrithiamine-induced thiamine deficiency (PTD), we have demonstrated that the hippocampus is functionally impaired: When PTD-rats are performing a spontaneous alternation task [49] or learning a nonmatching-to-position task [46] the rise in hippocampal acetylcholine (ACh) efflux is blunted relative to control rats. This impairment in hippocampal ACh efflux is only evident during behavioral testing as baseline levels of hippocampal ACh are normal in the PTD model.…”
mentioning
confidence: 99%
“…In recent years, some microdialysis studies have also examined the role of acetylcholine (ACh) release on learning and memory components during maze task performance (e.g. Pych et al, 2005;Roland and Savage, 2007). However, the poor temporal resolution of microdialysis sampling technique gives challenges to detect rapid biological processes in the brain during memory task performance.…”
Section: Introductionmentioning
confidence: 99%